Pilot trial using mass field-releases of sterile males produced with the incompatible and sterile insect techniques as part of integrated Aedes aegypti control in Mexico. - Abdiel Martín-Park; Azael Che-Mendoza; Yamili Contreras-Perera; Silvia Pérez-Carrillo; Henry Puerta-Guardo; Josué Villegas-Chim; Guillermo Guillermo-May; Anuar Medina-Barreiro; Hugo Delfín-González; Rosa Méndez-Vales; Santos Vázquez-Narvaez; Jorge Palacio-Vargas; et al. (Public Library of Science (PLoS), 2022)
Background The combination of Wolbachia-based incompatible insect technique (IIT) and radiation-based sterile insect technique (SIT) can be used for population suppression of Aedes aegypti. Our main objective was to evaluate whether open-field mass-releases of wAlbB-infected Ae. aegypti males, as part of an Integrated Vector Management (IVM) plan led by the Mexican Ministry of Health, could suppress natural populations of Ae. aegypti in urbanized settings in south Mexico. Methodology/principal findings We implemented a controlled before-and-after quasi-experimental study in two suburban localities of Yucatan (Mexico): San Pedro Chimay (SPC), which received IIT-SIT, and San Antonio Tahdzibichén used as control. Release of wAlbB Ae. aegypti males at SPC extended for 6 months (July-December 2019), covering the period of higher Ae. aegypti abundance. Entomological indicators included egg hatching rates and outdoor/indoor adult females collected at the release and control sites. Approximately 1,270,000 lab-produced wAlbB-infected Ae. aegypti males were released in the 50-ha treatment area (2,000 wAlbB Ae. aegypti males per hectare twice a week in two different release days, totaling 200,000 male mosquitoes per week). The efficacy of IIT-SIT in suppressing indoor female Ae. aegypti density (quantified from a generalized linear mixed model showing a statistically significant reduction in treatment versus control areas) was 90.9% a month after initiation of the suppression phase, 47.7% two months after (when number of released males was reduced in 50% to match local abundance), 61.4% four months after (when initial number of released males was re-established), 88.4% five months after and 89.4% at six months after the initiation of the suppression phase. A proportional, but lower, reduction in outdoor female Ae. aegypti was also quantified (range, 50.0-75.2% suppression). Conclusions/significance Our study, the first open-field pilot implementation of Wolbachia IIT-SIT in Mexico and Latin-America, confirms that inundative male releases can significantly reduce natural populations of Ae. aegypti. More importantly, we present successful pilot results of the integration of Wolbachia IIT-SIT within a IVM plan implemented by Ministry of Health personnel.